2012
DOI: 10.1002/hipo.22083
|View full text |Cite
|
Sign up to set email alerts
|

Divergent cellular pathways of hippocampal memory consolidation and reconsolidation

Abstract: The reconsolidation of memories after their retrieval involves cellular mechanisms that recapitulate much of the initial consolidation process. However, we have previously demonstrated that there are independent cellular mechanisms of consolidation and reconsolidation in the dorsal hippocampus for contextual fear memories. Expression of BDNF was required for consolidation, while Zif268 expression was necessary for reconsolidation. Given the dichotomy between the obvious mechanistic similarity and notable disso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 59 publications
(94 reference statements)
3
55
0
Order By: Relevance
“…Indeed, BDNF regulates mTOR-dependent translation (Takei et al, 2004) and controls the local synthesis of plasticity related proteins such as CaMKII, Arc, Homer 2 and GluR1 (Schratt, Nigh, Chen, Hu, & Greenberg, 2004;Slipczuk et al, 2009;Yin, Edelman, & Vanderklish, 2002), which are functionally linked to memory reconsolidation (Chia & Otto, 2013;Rich et al, 2016). Some reports, dealing mainly with fear-motivated learning tasks, indicate that BDNF participates in memory consolidation but not reconsolidation (Lee, Everitt, & Thomas, 2004;Lee & Hynds, 2013;Schulz-Klaus, Lessmann, & Endres, 2013). However, this differential involvement of BDNF in memory processing does not seem to be a common property of all kind of memories.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, BDNF regulates mTOR-dependent translation (Takei et al, 2004) and controls the local synthesis of plasticity related proteins such as CaMKII, Arc, Homer 2 and GluR1 (Schratt, Nigh, Chen, Hu, & Greenberg, 2004;Slipczuk et al, 2009;Yin, Edelman, & Vanderklish, 2002), which are functionally linked to memory reconsolidation (Chia & Otto, 2013;Rich et al, 2016). Some reports, dealing mainly with fear-motivated learning tasks, indicate that BDNF participates in memory consolidation but not reconsolidation (Lee, Everitt, & Thomas, 2004;Lee & Hynds, 2013;Schulz-Klaus, Lessmann, & Endres, 2013). However, this differential involvement of BDNF in memory processing does not seem to be a common property of all kind of memories.…”
Section: Discussionmentioning
confidence: 98%
“…Contextual fear memory reconsolidation and extinction have both been demonstrated to be critically dependent upon NMDA receptor activity (Suzuki et al 2004;Lee and Hynds 2013;Lee and Flavell 2014). The bidirectional effect of the same amnestic treatment, dependent upon the parameters of memory reactivation, indicates that the dissociable effects are mediated by impairments in different mnemonic processes (Lee et al 2006; de la The null point in contextual fear reactivation www.learnmem.org Fuente et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…No footshock was applied at either reexposure or test sessions. The aversive response (freezing) was automatically quantified during all sessions with a videotracking software (Viewpoint Life Sciences), and used as a memory index (Lee and Hynds 2013;Song et al 2016).…”
Section: Contextual Fear Conditioningmentioning
confidence: 99%
“…In light of our current findings, it may be tentatively suggested that exercise not only enhances BDNF, but may impact upon other brain transcription factors, such as Zif268 and upstream factors of de novo protein synthesis, where diverging pathways of hippocampal contextual fear memory consolidation and reconsolidation have been observed. It has been demonstrated that the dissociation between BDNF and Zif268 expression in memory consolidation and reconsolidation extends to the selective requirement for separate plasticity-associated gene expression of MEK and IKKa protein kinases, respectively, and a common involvement of NMDA receptors (Lee and Hynds 2013).…”
Section: Discussionmentioning
confidence: 99%